Interactive Learning Media with IMTAQ Content for Science Subjects in Class VII - Radhiatun Nafsi; Ramalis Hakim (International Journal of Educational Dynamics, 2022)
Science learning requires visualization of the objects, so teachers need to provide an integrated learning environment with technology and IMTAQ that allows students to drive their learning independently and understand the concepts better. This study aimed to produce valid and practical multimedia with IMTAQ content that can be effective for science subjects in grade VII. Data were obtained from the results of the media’s design, validity, practicality, and effectiveness through questionnaires, tests, and interviews. The results show that the developed interactive media is valid, practical, and effective because it gets a good response from teachers and students. It can also improve learning outcomes and affect the IMTAQ understanding of seventh-grade students.